Namibia : Recent Economic Developments and Selected Economic Issues. (IMF Staff Country Reports; Country Report ;, 1995)
This Recent Economic Developments and Selected Economic Issues paper provides a broad overview of the structure of Namibia's economy. It provides a detailed discussion of the structure and evolution of the productive base, recent trends in investment and savings performance, fiscal policies, monetary issues and policies, and external sector developments. The paper provides an assessment of Namibia's export performance and prospects for the future. The paper highlights that since independence in 1990, Namibia's real GDP has expanded at an annual compound rate of 3.8 percent, or 0.9 percent in per capita terms.